Post-harvest proteomics of grapes infected by Penicillium during withering to produce Amarone wine. (15th May 2016) - Lorenzini, Marilinda; Mainente, Federica; Zapparoli, Giacomo; Cecconi, Daniela; Simonato, Barbara
Highlights: Penicillium affects the grape quality during the post-harvest dehydration process. Grape proteins of healthy and Penicillium infected grapes were analyzed by 2-DE. Protein identification by MS analysis help to understand the pathogen attack mechanisms. Penicillium identified proteins may be used as specific markers of fungus infection. Detection of Penicillium grapes infection allow to prevent fungal growth. Abstract: The study of withered grape infection by Penicillium, a potentially toxigenic fungus, is relevant to preserve grape quality during the post-harvest dehydration process. This report describes the first proteomic analysis of Amarone wine grapes, infected by two strains of Penicillium expansum (Pe1) and Penicillium crustosum (Pc4). Protein identification by MS analysis allowed a better understanding of physiological mechanisms underlying the pathogen attack. The Pe1 strain had a major impact on Vitis vinifera protein expression inducing pathogenesis-related proteins and other protein species involved in energy metabolism. A greater expression of new Penicillium proteins involved in energy metabolism and some protein species related to redox homeostasis has been observed on grapes infected by Pc4 strain. Moreover, the new induced proteins in infected grapes could represent potential markers in withered grapes, thus creating the chance to develop case-sensitive prevention strategies to inhibit fungal growth.